2022
DOI: 10.1111/dme.14831
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cost‐effectiveness of Dexcom G6 real‐time continuous glucose monitoring system in people with type 1 diabetes in Australia

Abstract: Introduction: Real-time continuous glucose monitoring (rt-CGM) allows patients with diabetes to adjust insulin dosing, potentially improving glucose control. This study aimed to compare the long-term cost-effectiveness of the Dexcom G6 rt-CGM device versus self-monitoring of blood glucose (SMBG) and flash glucose monitoring (FGM) in Australia in people with type 1 diabetes (T1D).Methods: Long-term costs and clinical outcomes were estimated using the CORE Diabetes Model. Clinical input data for the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…It is possible that if the analyses had been performed from the societal perspective the ICURs may have been lower, as lost productivity costs in Denmark constituted 41% (EUR 1.77 billion) of the overall burden of T1D and T2D in 2011 11 . Moreover, the findings presented here align with those of a previous analysis in the Australian setting, in which rt‐CGM was projected to be cost‐effective compared with both SMBG and is‐CGM 29 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is possible that if the analyses had been performed from the societal perspective the ICURs may have been lower, as lost productivity costs in Denmark constituted 41% (EUR 1.77 billion) of the overall burden of T1D and T2D in 2011 11 . Moreover, the findings presented here align with those of a previous analysis in the Australian setting, in which rt‐CGM was projected to be cost‐effective compared with both SMBG and is‐CGM 29 …”
Section: Discussionsupporting
confidence: 73%
“…11 Moreover, the findings presented here align with those of a previous analysis in the Australian setting, in which rt-CGM was projected to be cost-effective compared with both SMBG and is-CGM. 29 The results from this study showed the health economic implications of the clinical outcomes from existing relevant studies. Specifically, randomized controlled trials and real-world evidence studies have shown that rt-CGM is associated with greater improvements in HbA1c, severe hypoglycaemia, and FoH relative to is-CGM.…”
Section: Discussionmentioning
confidence: 64%
“…The cost of rtCGM and rtCGM‐linked technologies remains significant and therefore becomes a barrier to access for those who do not get coverage by insurance or meet the required criteria for access and reimbursement via their national health system. It is important to recognize that the cost associated with rtCGM in iPDM may be offset by long‐term benefits in terms of reduced diabetes‐related complications and hospital admissions 76–78 . Mitigating health disparities in rtCGM and rtCGM‐linked diabetes technology adoption across diverse sociodemographic areas and ethnicities remains a challenge, necessitating a prioritized focus on bridging this gap.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term cost-effectiveness of Dexcom G6 real-time continuous glucose monitoring system in people with type 1 diabetes in Australia: Response to letter from Hellmund, Richard and Welsh, Zoe A letter from Hellmund, R. and Welsh, Z. was recently submitted to Diabetic Medicine expressing concern over the validity of utilizing the network meta-analysis (NMA) conducted by Pease et al (2020) in our paper entitled 'Longterm cost-effectiveness of Dexcom G6 real-time continuous glucose monitoring system in people with type 1 diabetes in Australia'. 1 The letter states the study relied on information for haemoglobin A1c (HbA1c) and quality of life (QoL) from Pease et al (2020). The Pease study is the largest NMA of its kind conducted to date, with inclusion of 52 eligible studies representing more than 3975 participants in the NMA.…”
Section: E T T E Rmentioning
confidence: 99%